2011
DOI: 10.1002/uog.8946
|View full text |Cite
|
Sign up to set email alerts
|

Cervical varices complicated by thrombosis in pregnancy

Abstract: We present a case of a 36-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…Our literature review identified eight other cases of cervical varices causing significant obstetrical hemorrhage (Table ). Although recognizing that limited conclusions may be drawn from these reports, it appears that varices are commonly associated with low placental implantations, maternal age ≥35, multiple gestations, and in vitro fertilization . A review of two other manuscripts cited as additional cases of varices in diethylstilbestrol‐exposed women suggests that these findings represent a different entity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our literature review identified eight other cases of cervical varices causing significant obstetrical hemorrhage (Table ). Although recognizing that limited conclusions may be drawn from these reports, it appears that varices are commonly associated with low placental implantations, maternal age ≥35, multiple gestations, and in vitro fertilization . A review of two other manuscripts cited as additional cases of varices in diethylstilbestrol‐exposed women suggests that these findings represent a different entity.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery planning should anticipate and prepare for possible massive transfusion and hysterectomy . Varices reportedly resolve within 3 days to 6 weeks following delivery . Absent any reports, recurrences and risks with future pregnancies remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations